Are Investments in Digitalisation of Agro-climate Advisory Service Profitable? - International Maize and Wheat Improvement Center (International Maize and Wheat Improvement Center, 2024)
Climate change and variability remain a challenge that poses a serious threat to people’s livelihoods, particularly in smallholder farming systems. Rainfedreliant smallholder agriculture is especially vulnerable to the adverse effects of climate change (Deressa et al., 2009; Simane et al., 2016). When these challenges are compounded with non-climate stressors, the effect would be devastating. Climate adaptation through the Agro-climate Advisory Service (ACAS) offers smallholder farmers the potential to improve evidence-based decisionmaking. Access to climate advisories potentially curbs the effect of climate risk and uncertainty on crop production and increases the resilience and adaptive capacity of farmers (Ouédraogo et al., 2018). However, the availability, accessibility, affordability, and reliability of advisory services remain concerns. As part of ongoing agro-climate advisories provision efforts and improve service provision efficiency, the International Maize and Wheat Improvement Centre (CIMMYT) has been implementing the Ethiopian Digital Agro-climatic Advisory Project (EDACaP) in collaboration with Green Agro-Solutions (GAS) PLC since 2019. The objective is to provide tailored ACAS to targeted smallholders to improve their livelihood by enhancing informed decision-making that reduces uncertainty involved in production decisions. ACAS has been channelled through the novel digital platform called LERSHA developed by GAS mainly in wheat-dominated production systems. The provision of ACAS involves investments and operational costs incurred by service providers. The profitability of the ACAS investment hasn’t been studied from the service providers’ (CIMMYT and GAS) point of view, and remains an empirical issue. To analyze whether investments in ACAS are profitable or not, the policy brief used two waves of survey datasets collected from 1,842 farm households that cover the Amhara, Oromia, SNNPR and Sidama regions. Investment outlay data was obtained from the GAS financial model and expert estimation was used for calculating operational costs relevant to climate advisory services. A discounted cash flow – Net Present Value (NPV) is used to analyse whether the multiperiod ACAS investments are profitable or not as it accounts for the time value of money compared to other methods. The result shows that the expected economic return (NPV) from investing in ACAS is 93,840,389,067 birr. On average, the additional return is 15,640,064,845 birr over six years @12% loan interest rate for the 2,950,000 target farmers targeted by the project over the years. The economic return analysis shows investing in ACAS is profitable. Averaged over six years, each recipient of the advisory service receives an additional return of about 12,000 birr/ha annually from the wheat value chain compared to those who don’t receive and utilise ACAS. Based on the results, it is suggested that digitalbased agro-advisory provision needs to be further strengthened and mainstreamed as it is beneficial for farmers. This is one of the pathways through which agricultural advisory provision would be modernised and gradually commercialised. On top of that, the bundled business model of GAS needs to be scaled up, where target farmers receive not only ACAS but other complementary services such as farm inputs and mechanisation services to address multifaced farmers’ needs. The collaboration of CIMMYT-GAS (a private sector player) in the provision of ACAS implies that they can play a crucial role in revitalising the agricultural extension service provision. This justifies the need to move onto a pluralistic extension system approach in the country under the oversee of the Ministry of Agriculture and relevant public institutions.